HBR's 10 must reads for mid-level managers - Willingham, Sofia; Vries, David de (Ascent Audio, 2023)
The pandemic, and the resultant ever-evolving landscape of hybrid work, highlighted that we're asking more of our mid-level managers than ever. You balance leading your team with maintaining your high-level individual performance. You provide feedback and coaching, support your people through tough times, field requests large and small, and communicate in every direction. Mid-level managers are the key to managing a hybrid workforce, leading innovation, managing talent, and helping your organization-and its people-adapt to our changing world. If you read (or listen to) nothing else on being an effective mid-level manager, listen to these ten articles by experts in the field. We've combed through hundreds of Harvard Business Review articles and selected the best ones to help you manage up and down, interpret and distill important messages, lobby for time and resources for key projects and players, and lead change-all while getting things done. This book will inspire you to: build teams and develop talent; transform your role from intermediary to innovator; encourage critical thinking; foster a culture of psychological safety; lead change by leveraging internal networks; understand the cognitive and emotional drain of having both high and low power; and form partnerships at every level of the organization.
Online resource; title from title details screen (O'Reilly, viewed August 8, 2023)
Keywords: Middle managers; Industrial management; Success in business; Cadres moyens; Gestion d'entreprise; Succès dans les affaires; Audiobooks; Livres audio